2022
DOI: 10.1007/s10639-022-11203-4
|View full text |Cite
|
Sign up to set email alerts
|

Educational Technology Adoption in Instructional Delivery in the New Global reality

Abstract: Educational technology is a discipline that has a lot of roles to play in the global education system yet, its services had been neglected over the years in Nigeria. The new global reality that was occasioned by the upsurge of COVID-19 has made educational technology a very consequential discipline with conspicuous roles to play in the face of such a global pandemic. COVID-19 has halted many human activities across the globe. Its effect in the education system has resulted to re-adjustment in the school calend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, it is concluded that educational practitioners require in-service training to actively participate in these changes. Additionally, the government is encouraged to adopt a systematic approach in procuring and installing ICT facilities that will facilitate the widespread implementation of educational technology in schools [42].This section discusses the results obtained from the surface pressure measurement study. The effects of angle of attack, Reynolds number and leading-edge bluntness are discussed in the next sub section.…”
Section: Theme 1: Technology Integration In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is concluded that educational practitioners require in-service training to actively participate in these changes. Additionally, the government is encouraged to adopt a systematic approach in procuring and installing ICT facilities that will facilitate the widespread implementation of educational technology in schools [42].This section discusses the results obtained from the surface pressure measurement study. The effects of angle of attack, Reynolds number and leading-edge bluntness are discussed in the next sub section.…”
Section: Theme 1: Technology Integration In Educationmentioning
confidence: 99%
“…Fig.2. Education systems have embraced educational technology, bringing about a paradigm shift from the traditional norms[42] …”
mentioning
confidence: 99%
“…This study investigated the complex consequences of technology adoption in Nigeria, giving insight into the dynamic interplay of societal, economic, and technological elements as the world navigates the post-pandemic era (Ogunji, Onwe, Ngwa, David, Olaolu & Cresantus, 2022). The specific objectives include examining the effects of society's growing reliance on technology on the economy, establishing how to remove barriers to equitable access to digital resources, analysing how technology is changing healthcare delivery, identifying what needs to be done to address cybersecurity concerns, and providing enlightening assistance to businesses, decision-makers, and the general public as they navigate the quickly evolving technological landscape (Ebekozien & Aigbavboa, 2021;Nwanyiuzor, Ngozi & Emelogu, 2023). The research encompassed a literature review comprises of theoretical framework, and empirical review, next section is the methodology consists of testing of hypotheses, followed by data results and analysis as well as discussion of findings, lastly conclusion and recommendations.…”
Section: Introductionmentioning
confidence: 99%